Building lower-carbon affordable housing: case studies from California. Issue 6 (18th August 2022) - Outcault, Sarah; Alston-Stepnitz, Eli; Sanguinetti, Angela; DePew, Ashley N.; Magaña, Cinthia
ABSTRACT: This research explores developers' experiences with lower-carbon multi-family affordable housing in California using three case studies that illustrate different pathways to decarbonization – improving efficiency, eliminating fossil fuel combustion for end-uses, and adopting a zero-net energy design. Qualitative analysis of in-depth interviews with stakeholders (e.g. developers, architects, consultants) involved in the development and management of three selected communities reveals several themes that influenced the design, construction and operation phases. One such theme includes uncertainty – about the future availability and cost of gas service and about operating costs and equipment performance – which was mitigated in part by adopting conservative energy modelling forecasts and elevating the role of energy consultants. Also discussed is how higher initial costs for lower-carbon designs were partially offset by higher rental income and favourable scoring for competitive financing mechanisms. Findings highlight the importance of alignment between project objectives and stakeholders' missions and having strong advocates on the development team. Electrifying water heating, the biggest technical challenge encountered, is discussed. Overall, the case studies illustrate various technical, economic and organizational challenges associated with decarbonizing affordable housing, examples of how they were overcome, and how these experiences inform development teams' plans to pursue lower-carbon designs in the future.